Investigating the spatiotemporal expression of CBTS genes lead to the discovery of tobacco root as a cembranoid-producing organ - Du, Zaifeng; Tian, Tian; Gao, Yulong; Guan, Jian; Ju, Fuzhu; Bian, Shiquan; Wang, Jiahao; Lin, Xiaoyang; Wang, Bingwu; Liao, Zhihua; Du, Yongmei; Zhang, Zhongfeng; et al. (Frontiers in Plant Science, 2024)
Tobacco cembranoids, known for their anti-insect and anti-fungal properties, were shown to be mainly present on the surface of leaves and flowers, being biosynthesized by their trichomes. It remains unclear whether they could be biosynthesized in other organs without trichomes. Cembratrien-ol synthases (CBTSs) catalyze the conversion of GGPP to CBT-ols and thus play an important role in cembranoid biosynthesis. This study here identified the CBTS family genes in tobacco and examined their spatiotemporal expression patterns. The CBTS genes showed diverse expression patterns in tobacco organs, with the majority highly expressed in leaves and a few highly expressed in flowers. The expression of CBTS genes were also correlated with the development of tobacco plants, and most of them showed the highest expression level at the budding stage. Furthermore, their expression is mediated by the JA (jasmonate) signaling in all tobacco organs. Several CBTS genes were found to be highly expressed in tobacco roots that have no trichomes, which prompted us to determine the cembranoid production in roots and other organs. GC-MS and UPLC assays revealed that cembranoids were produced in all tobacco organs, which was supported by the bioactivity assay results that almost all these CBTS enzymes could catalyze CBT-ol biosyntheis in yeast, and that the content ratio of CBT-ols and CBT-diols in tobacco roots was different to that in leaves. This work shed new insights on the transcription profiles of tobacco CBTS genes and provided a theoretical feasibility for metabolic engineering of tobacco roots for industrial production of cembranoids.